Islamic Education: As a Character Building Effort - Amin, Muhammad; Ritonga, Mahyudin; Nasrul, Wedy (Universitas Ahmad Dahlan, 2021)
This research aims to find out the patterns of students’ character building and factors that support and inhibit as faced by Islamic Education teachers in State Primary School 16 V Koto Timur District Padang Pariaman Regency. According to the objective, this research utilizes qualitative method with a descriptive approach. The data sources are a school principal, Islamic Education teachers, and Classroom teachers. The researchers use observation, interview, and documentation as the data collection techniques. The data analysis technique uses data reduction, classification, and presentation and conclusion drawing. It is known that Islamic Education is the students’ character-building effort. The character building pattern is done by integrating PAI (Islamic Education) and using uswah and hikmah method into character Education. In building students’ character, there are supporting and inhibiting factors that include school internal and external factors.